Posterior Reversible Encephalopathy Syndrome in Infection, Sepsis, and Shock - Bartynski, W.S.; Boardman, J.F.; Zeigler, Z.R.; Shadduck, R.K.; Lister, J. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: The cause of “posterior reversible encephalopathy syndrome” (PRES) is not established. We recently encountered several patients who developed PRES in the setting of severe infection. In this study, we comprehensively reviewed the clinical and imaging features in a large cohort of patients who developed PRES, with particular attention to those with isolated infection, sepsis, or shock (I/S/S).METHODS: The clinical/imaging features of 106 patients who developed PRES were comprehensively evaluated. In 25 of these patients, PRES occurred in association with severe I/S/S separate from transplantation. The clinical/imaging features (computer tomography, MR imaging, and MR angiography [MRA]) of the patients with I/S/S were further evaluated, including organ/tissue/blood culture results, mean arterial blood pressure (MAP) at toxicity, extent of cerebral edema, and presence of vasospasm.RESULTS: PRES occurred in association with I/S/S in 25 of 106 patients (23.6%), in addition to 4 other major clinical settings, including cyclosporine/FK-506 (post-transplant) neurotoxicity (46.2%), autoimmune disease (10.4%), postchemotherapy (3.7%), and eclampsia (10.4%). In the 25 patients with I/S/S, available cultures demonstrated a predominance of gram-positive organisms (84%). Blood pressure was “normal” at toxicity in 10 patients (MAP, 95 mm Hg); “severe” hypertension was present in 15 patients (MAP, 137 mm Hg). Extent of brain edema graded on imaging studies was greater in the normal MAP group compared with the severe hypertension group (P < .05). MRA demonstrated vasospasm in patients with severe hypertension and vessel “pruning” in the normal MAP group.CONCLUSION: Infection/sepsis/shock may be an important cause of PRES, particularly in relation to infection with gram-positive organisms.